Improve the voltage profile of the grid-integrated induction motor with a fuzzy-based voltage source converter - Jyothiraman, Neelagandan Virchuly; Sivachidambaranathan, Viraduchalam (International Journal of Power Electronics and Drive Systems (IJPEDS), 2024)
This article suggests installing a series compensator on grid-connected induction motors that allows for the ride-through of unbalanced voltage sag. Fuzzy logic controls the motor voltages in a standard three-phase voltage source inverter or voltage source inverter (VSI). An open-ended three-phase machine and the grid form a series connection for the VSI. The proposed system is well suited for uses where frequency variation is unnecessary, such as with large pumps or fans. There is no requirement for a direct current (DC) source or injection transformer when conducting an electric mutual coupling The severity of the sag in the grid voltage that will prevent EMC from shutting down is proportional to the load on the motors. An increase in the voltage of the DC link may be necessary if the voltage is not balanced. A 1.5 hp four-pole induction motor was used alongside grid voltage disturbances to test the proposed compensator's ride-through capability. Grid's current analysis demonstrates that the proposed system does not require the addition of a passive filter to achieve low levels of total harmonic distortion (THD). Additionally, the control strategy, component ratings, and analysis of the converter's output voltage operating principle and pulse width modulation technique are covered. The system's viability is shown via simulation and experimental results.